Islamic Scientific Education Based on Taurat, Zabur, Injil, Quran, and Hadith - Widiastutik, Farah Diba Setiana (Kaunia: Integration and Interconnection Islam and Science Journal, 2024)
The aim of this research is Allah's messages at QS Al Maidah 46, 66 – 68, and QS Ar Araf 170. At all that surah we know if moslem must used Taurat, Injil, Al Qur’an for law and human daily activity included education. Why Allah said like this it’s because grandchild of Prophet Ibrahim A.S had three imam, they are Rabi imam for Turat and Zabur, Paus Imam for Injil, Imam Makkah Imam for Al Qur’an. Purpose for this research is we can get complete knowledge for our theory and research product that no one can interrupted out knowledge especially at Isaiah and Moslem zone. This research used interview and secondary data from all Allah holly books and scientific journal since April 2019 until April 2024 with descriptive qualitative analyze. Result from this research are Isaiah and Moslem only had one God, and it’s Allah and Jesus is Allah's Prophet (Taurat Tanakh Tafsir Razaq, Zabur 1:1, Injil Genesisn 1:1, QS Al Ikhlas, HR Ibnu Mas’ud).The truth of human evolution theory is human come from Prophet Adam A.S and Eve, theory Darwinian comes from sabbath day (Taurat Kuzari 2 :20, Injil Imamat 26 : 2, Mathius 12:5, Ashabun Nuzul QS. Al Baqoroh 76, HR Abdirrahman Abdiilah bin Ibnu Mas’ud). Hawila location it’s Saudi Arabia (Taurat Samuel 15:7, Injil Genesis 2: 10 – 16, QS Al Baqoroh 35, HR Abu Daud, Tirmizi, Nasa’I : 4744).Complete Tarikh about Prophet Ibrahim A.S family, Prophet Ibrahim A.S had two wives, Sara and Hajar but if we used all holy books kitab Allah we know if Prophet Ibrahim had four wives, Sara mother of Europa, Hajar mother of Middle East Asia, Ketura mother of East Asia and ASEAN, Hajun mother of South Asia (Taurat Tanakh, Pirkei Avot 3:2, 5:21, Bamidbar Rabbah 13:2, Bereshit Rabbah 60:16, 61:1, Aggadat Bereshit 19:2, 3: 1-2, Injil Genesis 23:1, Genesis 16:1, Genesis 25:1, QS. Hujurat ; 11, QS. Ibrahim 37, QS Hud : 71, Kitab Al Qashah An Anbiya, HR Bukhari : 3112).Syaria Law Pirkei Avot 1:1, Zabur 1:2, 19:8, 119:1, Galatia5:18, Lukas 17:5, Mathius 5: 17 – 20, QS Ali Imran 3 – 4, QS Al Maidah 46,48,68, QS Ar Araf 170. Keluarga Nabi Adam A.S Sehendrin 38a: 9 – 18, Zabur 31 : 20, Genesis 1 – end, Exodus 1 – end, Barnabas lonsdale 117 – 120, QS Hijr 26, QS Al Maidah 27 – 32, HR Bukhari 3083. Money and monetary Miscnah Masser Sheni 2 : 5 – 9, Lukas 15 : 8 – 10, Mathius 20 : 1 – 16, QS Ali Imran 75, QS Yusuf 20, HR Bukhari. Daging halal Beitzah 32b: 11 – 12, Imamat 11:4, 47, Yesaya 16: 17, Ulangan 14 : 8, QS Al An’am 146. Last Prophet and Qiyamah Injil Barnabas lonsdale – laura halaman 117 – 120, QS An Nur : 146 : HR Syekh Taharsi so the conclusion is relation between knowledge and Taurat, Zabur, Injil, Al Qur’an, and Hadist, Isaiah and Moslem zone never can interrupted and all Imam father Rabi, Paus, Imam Makkah will accepted.